Modelling of the sequence of the technological process fulfillment in building construction - Андрушкявичюс, А.; Гинявичюс, Р.; Завадскас, Э. К. (Proceedings of National Aviation University (archive), 2021)
The tools for modelling of the sequence of the technological process fulfillment in building construction is developed with account on possibilities of compromising decisions and simultaneous decreasing of construction duration and cost, number of workers, increasing of productivity of the work.